2009
DOI: 10.1111/j.1365-2893.2009.01126.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of antiviral treatment initiation in hepatitis C virus‐infected patients: a Danish cohort study

Abstract: Predictive factors for initiation of antiviral therapy in chronically infected hepatitis C virus (HCV) patients are not fully elucidated. The aim of this study was to determine predictive factors for initiation of treatment with standard or pegylated interferon either alone or combined with ribavirin. A Danish cohort of individuals chronically infected with HCV was used and observation time was calculated from the date of inclusion in the cohort to date of death, last clinical observation, 1 January 2007, or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 22 publications
(35 reference statements)
1
34
1
Order By: Relevance
“…Butt and colleagues [23] found a treatment rate of 11.8% in unselected veterans who were older (median age 50 years) compared to our study sample but comparable with regard to the prevalence of comorbidities such as psychiatric disorders and drug and alcohol dependence. The cumulative chance of starting CHC treatment in a 5 year period has been estimated to 33% in a representative Danish CHC cohort study [24]. Among patients attending the specialist consultations of the Swiss Hepatitis C Cohort Study (SDDS) [25] a history of CHC related treatment has been reported in 31% of the whole cohort and in 51% in the subgroup of cirrhotics.…”
Section: Discussionmentioning
confidence: 99%
“…Butt and colleagues [23] found a treatment rate of 11.8% in unselected veterans who were older (median age 50 years) compared to our study sample but comparable with regard to the prevalence of comorbidities such as psychiatric disorders and drug and alcohol dependence. The cumulative chance of starting CHC treatment in a 5 year period has been estimated to 33% in a representative Danish CHC cohort study [24]. Among patients attending the specialist consultations of the Swiss Hepatitis C Cohort Study (SDDS) [25] a history of CHC related treatment has been reported in 31% of the whole cohort and in 51% in the subgroup of cirrhotics.…”
Section: Discussionmentioning
confidence: 99%
“…A former study, based on data from DANHEP [19], showed that patients infected with genotype 2/3, had an approximately 2.5 times higher chance of starting antiviral treatment, while older age at referral was a negative predictor of treatment initiation. The results in the present study, with relatively high SVR rates in genotype 1 patients age 45 or younger, could have implications for future treatment strategy in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…It includes data about individuals in Denmark who are chronically infected with hepatitis B and/or C, are 16 years of age or older, are followed in one of the 11 medical departments that monitor and treat patients with chronic hepatitis in Denmark, and have been seen at least once after 1 January 2002 in one of these departments. The database is described in detail elsewhere [19]. …”
Section: Methodsmentioning
confidence: 99%
“…After considering the contraindications for interferon-based therapy, a large number of patients diagnosed with chronic hepatitis C could not have treatment. Therefore, the proportion of patients initiating treatment was 31.0% in Swiss cohort study [9], and 33.0% in Danish cohort study [10]. …”
Section: Discussionmentioning
confidence: 99%